Pengaruh Sifat Inovasi Dan Teknologi Sistem Tanam Jajar Legowo Terhadap Keberhasilan Usahatani Padi Sawah (Suatu Kasus di Kecamatan Bojongpicung Kabupaten Cianjur) - Wawan Hermawan; Musli Rosmali; Euis Dasipah (OrchidAgri, 2023)
The purpose of this study was to determine the effect of the nature of innovation on the Jajar Legowo planting system technology, the influence of the Jajar Legowo planting system technology on the success of lowland rice farming, the influence of the nature of innovation and Jajar Legowo technology on the success of lowland rice farming. This study used a survey method with the unit of analysis being farmers implementing Integrated Crop and Resource Management Technology in Bojong Picung District, Cianjur Regency. The sampling technique was carried out by random sampling of 110 respondents. The collected data were analyzed using path analysis, the analysis was adjusted according to the results of hypothesis testing. The results showed that the factors of the nature of innovation and the technology of the Legowo rice planting system simultaneously had a significant effect on the success of farming by 92.1%. The remaining 7.9% is influenced by other factors not examined in this study.